Mechanisms of microbiota-gut-brain axis communication in anxiety disorders - Jiang, Min; Kang, Li; Wang, Ya-Li; Zhou, Bin; Li, Hong-Yi; Yan, Qiang; Liu, Zhi-Gang (Frontiers in Neuroscience, 2024)
Anxiety disorders, prevalent mental health conditions, receive significant attention globally due to their intricate etiology and the suboptimal effectiveness of existing therapies. Research is increasingly recognizing that the genesis of anxiety involves not only neurochemical brain alterations but also changes in gut microbiota. The microbiota-gut-brain axis (MGBA), serving as a bidirectional communication pathway between the gut microbiota and the central nervous system (CNS), is at the forefront of novel approaches to deciphering the complex pathophysiology of anxiety disorders. This review scrutinizes the role and recent advancements in the MGBA concerning anxiety disorders through a review of the literature, emphasizing mechanisms via neural signals, endocrine pathways, and immune responses. The evidence robustly supports the critical influence of MGBA in both the development and progression of these disorders. Furthermore, this discussion explores potential therapeutic avenues stemming from these insights, alongside the challenges and issues present in this realm. Collectively, our findings aim to enhance understanding of the pathological mechanisms and foster improved preventative and therapeutic strategies for anxiety disorders.